Mucocele of the Appendix Secondary to Chronic Appendicitis: A Case Report - Parvat Kuwar Chhetri; Frederick M. Tiesenga; Priscilla E. Mawudzro (Clinical Case Reports)
ABSTRACT Chronic appendicitis leading to mucocele of appendix, though rare and often mimicking malignancy, can present with benign histopathology. Multidisciplinary correlation of clinical, imaging, intraoperative, and histopathological findings is critical to avoid misdiagnosis and guide conservative management in atypical presentations.